2020
DOI: 10.1093/jn/nxaa209
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Scoping Review of How Healthcare Organizations Are Facilitating Access to Fruits and Vegetables in Their Patient Populations

Abstract: Background There is compelling evidence on the impact of diet as preventative medicine, and with rising health care costs healthcare organizations are attempting to identify interventions to improve patient health outcomes. Objectives The purpose of this systematic scoping review was to characterize existing healthcare organization–based interventions to improve access to fruits and vegetables (F&V) for their patient popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 74 publications
1
44
0
2
Order By: Relevance
“…Produce prescription programs have been implemented in primary care settings to address FI and diet quality and many targeting adults have been evaluated for feasibility and impact [ 25 , 26 ]. Few programs specifically addressing families with young children have been evaluated and all, except one [ 27 ], have used a client-choice, external-to-the-home model of providing supplemental produce resources (e.g., farmer’s market or food pantry vouchers) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Produce prescription programs have been implemented in primary care settings to address FI and diet quality and many targeting adults have been evaluated for feasibility and impact [ 25 , 26 ]. Few programs specifically addressing families with young children have been evaluated and all, except one [ 27 ], have used a client-choice, external-to-the-home model of providing supplemental produce resources (e.g., farmer’s market or food pantry vouchers) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current challenges include infrequent screening in health care systems or the electronic health record for food security or especially diet quality, no broad coverage for Food Is Medicine interventions in Medicare and Medicaid, and a dearth of standardized toolkits to provide health care executives and clinicians with pragmatic implementation frameworks. Conversely, the concept of Food Is Medicine is gaining public visibility; is founded on compelling evidence for health benefits of phytonutrientrich, minimally processed foods; fits into Affordable Care Act requirements for Community Health Needs Assessments by nonprofit hospitals; and is foundational to addressing social determinants in health care (2). Growing shifts toward valuebased accountable care and risk-sharing payments should accentuate this interest.…”
mentioning
confidence: 99%
“…Growing shifts toward valuebased accountable care and risk-sharing payments should accentuate this interest. Robust evaluation of ongoing and future interventions is essential to assess dietary, health, and utilization impacts, hopefully accelerating our understanding of the many research gaps identified by Veldheer et al (2).…”
mentioning
confidence: 99%
“… 2 Strategies to help reduce food insecurity among patients include supporting enrollment in federal food assistance programs, providing information and access to on-site food pantries, referring patients to local community resources (eg, food banks), and increasingly, offering referrals for direct financial incentives or subsidies for fruits and vegetables. 3 , 4 The last 5 years have seen tremendous growth in the prevalence and evaluation of such programs, often referred to as produce prescriptions, though it is difficult to quantify since so many operate within health systems or local community groups. A recent landscape analysis reported more than 100 programs launched between 2010 and 2020.…”
Section: Introductionmentioning
confidence: 99%